Campaign Promises as Political Contracts: Legal Analysis of Public Officials' Accountability in Governance (Legtimacy: Journal of Law and Islamic Law, 2025)
This article reconceptualizes campaign promises as binding political contracts and examines the accountability of Indonesian public officials within governance structures. Employing a normative–juridical methodology and comparative legal analysis, it reviews constitutional provisions, administrative statutes, and landmark judicial decisions most notably Central Jakarta District Court Decision No. 17/PDT.G/2009/PN.JKT.PST to identify enforcement gaps. The study integrates social contract theory, principal–agent accountability frameworks, and Bovens’ accountability model to develop a hybrid mechanism that combines legislative amendments, enhanced parliamentary oversight, expanded judicial review, and civil society monitoring. Key findings reveal systemic failures in fulfilling electoral commitments, evidenced by high-impact cases in infrastructure prioritization, employment pledges, fiscal management, anti-corruption initiatives, and intellectual property enforcement. Quantitative analysis of a Legal Accountability Impact Score confirms that job creation promise violations and tax policy contradictions represent the most severe accountability deficits. The research demonstrates that Indonesia’s existing constitutional and administrative law foundations can support enforceable political contract mechanisms but require institutional reforms to operationalize them effectively. By aligning electoral commitments with legal obligations, the proposed framework strengthens democratic governance and the rule of law